2006
DOI: 10.1089/lap.2006.16.113
|View full text |Cite
|
Sign up to set email alerts
|

Role of Appendectomy in Laparoscopic Training

Abstract: Laparoscopic appendectomy can be safely incorporated into the training of surgical residents under the supervision of experienced surgeons. Laparoscopic appendectomy also provides knowledge of the basics of laparoscopic technique before going on to more complex operations.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(19 citation statements)
references
References 24 publications
1
16
0
Order By: Relevance
“…149,150 Surrogate markers to assess technical competence are not a new method to assess surgical performance, and previous attempts have been made to assess the performance of certified surgeons, using patient morbidity and mortality as surrogate outcomes. [151][152][153][154] The major drawback of the assessment methods included here is whether surrogate markers are a true measure of technical competence. There are many other variables at work during a procedure; perhaps the time to complete a procedure, the cecal intubation rate, or the strength of tendon repair are based more on patient's characteristics and the periprocedure environment (ie, team dynamics, bowel preparation) than on resident technical competence.…”
Section: Discussionmentioning
confidence: 99%
“…149,150 Surrogate markers to assess technical competence are not a new method to assess surgical performance, and previous attempts have been made to assess the performance of certified surgeons, using patient morbidity and mortality as surrogate outcomes. [151][152][153][154] The major drawback of the assessment methods included here is whether surrogate markers are a true measure of technical competence. There are many other variables at work during a procedure; perhaps the time to complete a procedure, the cecal intubation rate, or the strength of tendon repair are based more on patient's characteristics and the periprocedure environment (ie, team dynamics, bowel preparation) than on resident technical competence.…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that laparoscopic appendectomy can be safely incorporated as part of the surgical training program for residents in a teaching hospital [8]. For the trainee, it provides a valuable opportunity to master basic laparoscopic skills [7,13]. There has been some concern about the safety of resident-performed appendectomy [11].…”
Section: Discussionmentioning
confidence: 99%
“…Appendectomy has traditionally been regarded as a fundamental step in a junior surgeon's training. An analogous role must be claimed for LA, as it is fundamental for acquiring dexterity and skill in laparoscopy, necessary to tackle advanced minimally invasive operations [44]. Prospective studies on residents' outcomes in appendectomy operations have stated the learning curve is completed after twenty operations [45] (level III).…”
Section: The Training Issuementioning
confidence: 99%